Mission reliability driven functional healthy state modeling approach considering production rhythm and workpiece quality for manufacturing systems. (October 2022) - Wang, Wenzhuo; He, Yihai; Liao, Ruoyu; Cai, Yuqi; Zheng, Xin; Zhao, Yu
Highlights: A new connotation of the functional healthy state of the manufacturing system is proposed. A mission reliability model considering the production rhythm and workpiece quality is presented. A mission reliability driven functional healthy state quantitative model is established. A ferrite phase shifting unit manufacturing system healthy prognosis industrial example is given. Abstract: The core function of a manufacturing system is to continuously and stably output products conformed to specified production rhythm and quality, which can meet the requirements of production tasks. However, previous studies of the overall state of a manufacturing system mostly focused on the basic reliability, but disregarded the operational characteristics and functional demands of a manufacturing system. Therefore, a novel mission reliability driven functional healthy state modeling approach considering the production rhythm and workpiece quality for a manufacturing system is proposed. First, the operational mechanism oriented function realization is expounded. On this basis, the connotations of the mission reliability and functional healthy state are defined respectively. Second, the mission reliability model considering the production rhythm and workpiece quality is constructed based on the established quantitative models of the production rhythm output capacity and workpiece quality qualified capacity. Third, driven by mission reliability, the overall functional healthy state modeling method of a manufacturing system is proposed. Finally, a numerical study of a ferrite phase shifting unit manufacturing system is presented to demonstrate the accuracy and effectiveness of the proposed methods.